Simulation-based non-linear vibration model for damage detection in RC beams. Issue 8 (3rd July 2021) - Hanif, Muhammad Usman; Ibrahim, Zainah; Jameel, Mohammed; Ghaedi, Khaled; Hashim, Huzaifa
Abstract: This study presents a simulation-based method for damage detection in reinforced concrete beam-type structures. Reinforced concrete bridges are constantly exposed to dynamic loading, thus leading to deterioration before their design life. A novel damage assessment procedure has been presented, which uses the changes in non-linear vibration characteristics from computational model for damage assessment. A constitutive model is proposed, the parameters of which can be developed from compressive strength from laboratory test, and implemented in FE modelling of an RC beam. Incremental static damage is simulated in the beam, after which the non-linear behaviour is detected using harmonic excitation. The non-linear behaviour from simulation is characterised and used in proposing a damage detection method that does not rely on the baseline data of the structure. The methodology is validated experimentally and compared with conventional linear frequency-shift-based damage detection method. Resultantly, the proposed method is simple, computationally efficient, shows good agreement with the published studies on cracked vibration behaviour and has promising prospects in addressing inverse engineering problem in structural health monitoring of RC structures.